PENGARUH KEADILAN ORGANISASI, KEPUASAN KERJA DAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR TERHADAP TURNOVER INTENTION KARYAWAN PADA NEGARI COFFEE LUWAK - Saraswati, Ni Putu Ayu Sintya; Ribek, Pande Ketut (JUIMA : JURNAL ILMU MANAJEMEN, 2018)
The success of a company in achieving its goals is largely determined by the ability of the company in managing its resources. The study was conducted in Negari Kopi Luwak. The sample in this research is all employees of Negari Kopi Luwak which amount to 47 people. Data were collected by observation, interview and questionnaire distribution. The data analysis technique uses variance based method or SEM base component called partial least square (PLS). The results of research is organizational justice has a significant positive effect on employee job satisfaction. Organizational justice has no significant positive effect on organizational citizenship behavior. Organization justice has a significant negative effect on turnover intention. Job satisfaction has an insignificant positive effect on organizational citizenship behavior. Job satisfaction has a significant negative effect on turnover intention and organizational citizenship behavior has an insignificant positive effect on turnover intention.